Hormonal determinants of erectile dysfunction and lower urinary tract symptoms in middle-aged and elderly men with prediabetes. (2nd October 2015) - Rabijewski, Michał; Papierska, Lucyna; Kuczerowski, Roman; Piątkiewicz, Paweł
Abstract: Objectives : Erectile dysfunction (ED) and lower urinary tract symptoms (LUTS) are common in diabetic men. The aim of this study was to investigate hormonal determinants, the prevalence and severity of ED and LUTS in middle-aged and elderly men with prediabetes (PD). Methods : We investigated 176 men with PD and 184 healthy peers. PD was defined according American Diabetes Association. ED according IIEF scale and LUTS according IPSS scale were assessed. Total testosterone (TT), calculated free testosterone (cFT), dehydroepiandrosterone sulfate (DHEAS) and insulin-like growth factor 1 (IGF-1) were measured. Results : The prevalence of ED in patients with PD was higher than in control group (30 versus 24%) as well as the prevalence and severity of ED and LUTS in elderly (60–80 years) and middle-aged (40–59 years) men with PD was higher than in healthy peers. In middle-aged pre-diabetic men, the more severe LUTS symptoms were associated with low TT and DHEAS, while in elderly men with low cFT and DHEAS. The higher prevalence of ED in middle-aged men with PD was associated with cFT and DHEAS, while in elderly pre-diabetic men with TT and IGF-1. Conclusions : The prevalence and severity of LUTS and ED symptoms were higher in pre-diabetic men than in healthy peers. Hormonal determinants of these symptoms are different in middle-aged and elderly patients with PD.